Obtenção de nanoclusters fluorescentes de ouro em puliuretanos a base de ß-ciclodextrinas - Vasconcelos, Diego Andrade (2015)
An increase in the research interest related to nanomaterials, with gold-based ones being among the most studied, have been noticed. These materials are higlighted mainly due to their particular features acquired when sizes are reduced to nanometric scale. Metallic nanosystems have interesting physical properties such as photon emission and absorption, quantum confinement, among other optical phenomena. Many research works foccus on the synthesis, controlling sizes of these metallic systems. Gold clusters have been employed for diverse functions such as molecular dyagnosis,, detection of chemical/biological agents, bioengineering, ion sensing, catalysis of chemical reactions, to name a few uses. Thus, this work is foccused on the synthesis and characterization of Au15 clusters using glutathione as stabilizer, coupling the clusters to the cavities of a cyclodextrins-derived polymer. The objectives are to increase the yield on gold clusters and to avoid their formation outside the cavities of the cyclodextrin-derived polymer, to study the catalytic effect of the gold clusters in the reduction of 4-nitrophenol (PNP) by NaBH4 to 4-aminophenol (PAP). Optical UV/visible absorption, photoluminescence (PL), fourier-transform infrared spectroscopy and transmission electron microscopy (MET) were used to characterize the samples. It was observed that the polymer matrix used allowed the synthesis of Au15 clusters with characteristic absorption at 405 nm, indicative of clusters with number of atoms near 15, as well as a strong emission both in solid state and in solution. The catalytic activity of the clusters obtained in the PNP reduction to PAP was demonstrated.